Usos e impactos de impressos europeus na configuração do universo pictórico mineiro (1777-1830) - Camila Fernanda Guimarães Santiago (2009)
The present doctoral thesis studies the relationships between the European prints and the pictorial production in Minas Gerais during the development of the artistic language known as Rococo. The thesis also analyses the impacts of the handling of European prints – books and engravings – on people involved with artistic creation. Examining the artists' post mortem inventories, the presence of volumes and prints that were manipulated for the improvement of the picturals creations was revealed. It is necessary to consider that the use of prints at that time was not limited to the cognitive tasks now understood as reading – intellectual and systematic decoding of alphabetical signs –, but it embraced varied practices: the products of the European presses were seen in order to learn the textual teachings that they contained as well as in order to observe the images that composed them. Three types of printed papers are, here, privileged: isolated prints, above all saints' registrations, books about painting practices, like the treatises, and illustrated religious books. The books about painting listed on artists’ inventories were read, studied, and the technical knowledge and its aesthetics conceptions were compared with the paintings made by their owners and contemporaries.